University Campus Peer Support Centres: Benefits for Student Emotional and Mental Well-Being - Brar, Ikdip Kaur.; Ryu, Jae Eun; Shaikh, Kamran; Altman, Ashlie; Ng, Jeremy (The Meducator, 2012)
Within undergraduate student populations, there has been a rise in the incidence of mental health issues such as depression and anxiety. These problems have been shown to negatively impact emotional wellbeing and academic success.1 Many elements of the undergraduate experience, including stressful transitions from high school to first year, contribute to mental health problems amongst this student body. Peer support is a relatively recent resource for universities to address growing mental health concerns on campus. Peer support, which involves trained students who voluntarily provide emotional support to peers, offers a unique function to student mental health. It can be useful throughout a student’s undergraduate career and is also beneficial to those who provide the support. While it may not replace professional mental health services, it may be a significant addition to the existing student wellness support systems on university campuses today.